Pharmaceutical Nanoemulsions and Their Potential Topical and Transdermal Applications: Pharmaceutical nanoemulsions potential applications - Samira Sadat Abolmaali; Ali Mohammad Tamaddon; Fakhr Sadat Farvadi; Saeed Daneshamuz; Hamidreza Moghimi (Iranian Journal of Pharmaceutical Sciences, 2011)
Topical and transdermal drug delivery systems are noninvasive and can be self-administered with the minimization of side-effects, have received increased attention during the past few years. Nanoemulsions, emulsions sized between 20-200 nm with narrow distributions, offer several advantages for topical and transdermal delivery of pharmaceutical agents including controlled droplet size, the ability to efficiently dissolve lipophilic drugs, enhanced skin permeation and extended release of lipophilic and hydrophilic drugs. Moreover, they exert good sensorial and physical properties such as complete dispersion on skin and skin hydration in cosmetic products. The review deals with nanoemulsion applications in topical and transdermal drug and gene delivery.